Pengaruh Penambahan Abu Batu Terhadap Mix Design Campuran Beton Program Studi Teknik Sipil, Institut K-225 - Mhd Almahi; Yelfidar Yelfidar; Syaiful Hendri Rawi (Jurnal Sipil Terapan, 2023)
Basically, the ingredients for forming concrete consist of cement, water, and aggregate, namely fine aggregate and coarse aggregate. The aggregates commonly used are natural aggregates, namely sand as fine aggregate and gravel or crushed stone as coarse aggregate. Sand as fine aggregate is obtained from mining processes in nature, especially in Indragiri Hulu district, sand mining occurs almost along the Indragiri river. Rock ash is generally dark in color (blackish gray), and consists of fairly coarse grains. When compared to sand, rock ash has a cheaper price. The method used in this study is the experimental method, namely research that aims to investigate causal relationships between one another and compare the results so as to make an innovation. The results of the tests that have been carried out by the author on variations in the addition of stone ash to the concrete mixture for fine aggregate with variations of 25%, 50% and 75%. The results of laboratory tests in this study found that the optimum percentage of rock ash as a substitute for sand was a variation of 50% rock ash with a compressive strength of 28 days of 19.60 Mpa. Rock ash on 50% test specimen can be used as a substitute for sand because in terms of compressive strength with the quality provisions K-225 meets the requirements with a value of 19.60 MPa.